AFFIXATION IN LANGUAGE LEARNING - Shaymardanova Farangiz; Tursunova Munira; Furqatova Bonu (TADQIQOTLAR, 2026)
Annotation This article discusses the concept of affixation and its importance in language learning. Affixation is a word-formation process that involves adding prefixes and suffixes to base words to create new meanings. The study highlights how affixation helps learners expand vocabulary, improve grammar skills, and understand word structure. It also explains how affixation supports effective communication and language development.